Analisis Tingkat Planned Happenstance Skill pada Santri Putri di Pondok Pesantren - Subhan, Nurul Izzah (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2024)
Planned happenstance skills are skills to actively create, recognize, and utilize opportunities that arise by chance in order to make career choices and achieve life goals. Planned happenstance skills are skills needed in dealing with career changes in the era of disruption, especially in school-age adolescents who are in transition to careers after graduation. Not only students in public schools, santri in boarding schools also need skills in career planning because it can help them in determining career choices that are in accordance with their interests and talents. This research uses quantitative descriptive method. The subjects of this study were adolescent students aged 16-17 years in one of the Islamic Boarding Schools in South Sulawesi Province, Indonesia. Based on the results of this study, it can be seen that the planned happenstance skills of the students as a whole are in the Moderate category with a score of 70.52. Thus, it is hoped that there will be efforts to improve planned happenstance skills in students so that students can adjust their careers by utilizing these skills. One of the ways that can be done is by providing career counseling guidance services.